Devoção e sociabilidade negra em uma zona de imigração europeia: a irmandade de Nossa Senhora do Rosário e São Benedito de São Leopoldo (RS, 1852-1904) - Baldasso, Camille Chies (Universidade do Vale do Rio dos Sinos, 2023)
This paper is the result of a documentary research with rare and unpublished sources produced by members of the Irmandade de Nossa Senhora do Rosário e São Benedito de Pretos e Pardos de São Leopoldo. From the Compromisso and the Livros de Atas of this Brotherhood, a micro-historiographical analysis was developed to understand how this space of sociability, agency, negotiations and conflicts was built and maintained. Through the daily life fragments of the devotees of the Rosary, it was possible to think about the interdependencies and interethnic relations between enslaved and egressed captives with their masters, deepening the black presence in a European immigration zone and contributing to the construction of a more racialized and diverse history of Vale do Rio dos Sinos and Rio Grande do Sul as a whole. Through the bias of devotion and black associations, we approach the enslaved, free and freed black population of São Leopoldo in the 19th century as characters in their own stories and actively engaging in the society in which they were inserted. Not as wounded or passive victims of the injustices they have faced, but as human beings. Complex, plural and dynamic people who revolted, organized themselves, had choices and possibilities.
Keywords: Irmandades leigas; São Leopoldo; Agências; Associativismo negro; Devoção; Lay brotherhoods; Agencies; Black associations; Devotion; ACCNPQ::Ciências Humanas::História